Konsep Pemanfaatan Sumber Daya Alam Perspektif Alquran - Ahmad Giri Ainuddin; Ni’matul Izza (Universitas Muhammadiyah Mataram, 2025)
Abstract: The utilization of natural resources is a crucial issue in maintaining ecosystem balance and the sustainability of human life. This study examines the use of natural resources that, while beneficial to humans, may cause environmental degradation if exploited excessively. Character education based on Islamic environmental ethics is deemed essential in fostering a moderate, responsible attitude grounded in the principle of ihsan. This research employs a qualitative approach with a descriptive-analytical library study method, focusing on Qur’anic verses, their exegetical interpretations, and relevant literature concerning natural resource utilization. The findings reveal that Muslim scholars interpret nature as God’s creation that must be utilized wisely for the common good, rather than for individual or group interests that may lead to destruction. Theoretically, this study contributes to the development of the concept of environmental ethics from an Islamic perspective, particularly by emphasizing moderation, responsibility, and ihsan as the foundation of natural resource utilization. Practically, it provides implications for strengthening character formation in both schools and communities through the internalization of Islamic environmental values, Furthermore, it serves as a foundational consideration for policies related to the utilization of natural resources.Abstrak: Pemanfaatan sumber daya alam menjadi isu penting dalam menjaga keseimbangan ekosistem dan keberlanjutan kehidupan manusia. Penelitian ini membahas pemanfaatan sumber daya alam yang bermanfaat bagi manusia namun berpotensi merusak lingkungan jika dilakukan secara eksploitatif. Pendidikan karakter berbasis etika lingkungan perspektif Islam dipandang penting untuk membentuk sikap moderat, bertanggung jawab, dan berlandaskan prinsip ihsan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan deskriptif-analitis, mengkaji ayat dan tafsir Alquran dan literatur relevan mengenai pemanfaatan sumber daya alam. Hasil penelitian menunjukkan bahwa ulama menafsirkan alam sebagai ciptaan Allah yang harus dimanfaatkan secara bijak untuk kemaslahatan bersama, bukan untuk kepentingan individu atau kelompok yang merusak. Secara teoritis, penelitian ini berkontribusi terhadap pengembangan konsep etika lingkungan perspektif Islam, khususnya dengan menekankan sikap moderat, bertanggung jawab, dan ihsan sebagai dasar pemanfaatan sumber daya alam. Penelitian ini juga memberikan implikasi secara praktis pada penguatan karakter baik di sekolah atau masyarakat melalui proses internalisasi nilai-nilai etika lingkungan perspektif Islam, juga sebagai dasar kebijakan terhadap hal-hal yang berkaitan dengan pemanfaatan sumber daya alam.